Dampak MSG (Monosodium Glutamate) dan Jenis Bahan Organik terhadap Kandungan N, P, dan K pada Pupuk Cair: The Impact of MSG (Monosodium Glutamate) and Types of Organic Materials on the N, P, and K Content of Water Fertilizer - Subagiyo, Awalia Azizah; Arifin, Mochamad; Priyadarshini, Rossyda (Biofarm : Jurnal Ilmiah Pertanian, 2025)
Monosodium Glutamate is a chemical that can be used as an economical fertilizer with affordable prices and has a positive impact on plants. The selection of the main organic material in making fertilizer is the most important thing to make a fertilizer that has a quality content value. The presence of several contents in MSG is considered to be able to help improve the quality of liquid fertilizer combined with several different organic materials (cow, chicken and compost) to help meet the elements of N, P, and K as a source of nutrition during the plant growth process. The purpose of this study was to determine the combination of treatments between MSG and various organic materials to produce the highest NPK elements. This study was conducted at the Jombang Agriculture Service Laboratory using the Randomized Block Design (CRD) method with 2 treatment factors, namely Organic Material (M) and MSG Concentration (D). M1 Cow Manure M2 Chicken Manure and M3 Compost. D0 Control D1 2gr / l D2 4gr / l D3 6gr / l. There are 12 treatment combinations with 3 replications so that there are 36 experimental units. The data obtained were then analyzed using the Analysis Of Variance (ANOVA) method and continued with the 5% BNT Test (Smallest Real Difference). The results showed that the combination of MSG and various organic materials had a significant effect on the NPK nutrient content. The conclusion obtained was that the combination of organic chicken manure and MSG concentration of 4gr/l (M2D2) gave the highest NPK value.Keywords: monosodium glutamate, organic material, liquid fertlizer, nutriens